Typing of HLA susceptibility alleles as complementary tool in diagnosis of controversial cases of pediatric celiac disease - Ruera, Carolina Naymé; Guzman, Luciana; Menendez, Lorena; Orellano, Laura; Girard Bosch, María Cecilia; Catassi, Carlo; Chirdo, Fernando Gabriel (Frontiers in Nutrition, 2025)
ObjectivesDiagnosis of celiac disease (CeD), an immune-mediated disorder, is based on clinical presentation, a panel of serological markers, and the histopathological findings in duodenal biopsies. Commonly, pediatric CeD patients fulfill these criteria for diagnosis. However, lack of correlation between serology tests and histology, or no accessible biopsies because of clinical conditions or during the COVID pandemic, are conditions that led to inconclusive diagnoses. Since the majority of CeD patients carry HLA-DQ2 and/or DQ8 alleles, HLA testing is used as a complementary tool in diagnosis though is costly and not broadly available for gastroenterology centers.MethodsWe performed a retrospective study to assess the performance of HLA testing when applied to selected groups of patients who could not be definitely diagnosed following the common algorithm. Eighty patients underwent testing for CeD-related HLA-DQ2 and DQ8 alleles.ResultsHLA typing contributed to diagnosis in 34 patients with positive serology but normal mucosa or those who presented negative serology or slightly positive serology (less than 3 times ULN) and duodenal histopathological changes. In patients with normal histology and negative or slightly positive serology, or those who did not undergo intestinal biopsy (39 in total), HLA typing contributed to CeD diagnosis in 23 cases, only 16 patients were admitted for a clinical follow-up program.ConclusionHLA-DQ typing supported the diagnosis in 57 of 80 children (71.2%) with previously inconclusive results, providing a beneficial approach for diagnosing celiac disease (CeD) in selected cases.